Nanosheets‐Assembled CuSe Crystal Pillar as a Stable and High‐Power Anode for Sodium‐Ion and Potassium‐Ion Batteries. Issue 20 (2nd April 2019) - Lin, Hezhe; Li, Malin; Yang, Xu; Yu, Dongxu; Zeng, Yi; Wang, Chunzhong; Chen, Gang; Du, Fei
Abstract: Thanks to low costs and the abundance of the resources, sodium‐ion (SIBs) and potassium‐ion batteries (PIBs) have emerged as leading candidates for next‐generation energy storage devices. So far, only few materials can serve as the host for both Na + and K + ions. Herein, a cubic phase CuSe with crystal‐pillar‐like morphology (CPL‐CuSe) assembled by the nanosheets are synthesized and its dual functionality in SIBs and PIBs is comprehensively studied. The electrochemical measurements demonstrate that CPL‐CuSe enables fast Na + and K + storage as well as the sufficiently long duration. Specifically, the anode delivers a specific capacity of 295 mA h g −1 at current density of 10 A g −1 in SIBs, while 280 mA h g −1 at 5 A g −1 in PIBs, as well as the high capacity retention of nearly 100% over 1200 cycles and 340 cycles, respectively. Remarkably, CPL‐CuSe exhibits a high initial coulombic efficiency of 91.0% (SIBs) and 92.4% (PIBs), superior to most existing selenide anodes. A combination of in situ X‐ray diffraction and ex situ transmission electron microscopy tests fundamentally reveal the structural transition and phase evolution of CuSe, which shows a reversible conversion reaction for both cells, while the intermediate products are different due to the sluggish K + insertion reaction. Abstract : Nanosheets‐assembled CuSe crystal pillars (CPL‐CuSe) are synthesized and their dual functionality in sodium‐ion (SIBs) and potassium‐ion batteries are comprehensively studied. Benefiting from the multidisciplinary achievements in aspects of crystal phase tailoring and morphological characteristics, CPL‐CuSe demonstrates superior electrochemical performances and proves to be a promising candidate as the anode for both sodium‐ion and potassium‐ion batteries.